Characterizing prospective Secondary Education Mathematics Teachers’ self-efficacy - Salomón-Plata, María Soledad (2024)
[Objective] The aim of this paper is to analyze the self-efficacy of prospective Secondary School Mathematics Teachers at the end of their initial teacher training. [Methodology] The sample was 98 prospective Secondary School Mathematics Teachers who were studying in a University Master’s program for Secondary Education Teachers. The data were their written reflections, which were organized into information units and classified according to the five sources of self-efficacy collected from specialized literature: professional knowledge; classroom practice; physiological, affective and motivational states; cooperation with colleagues and parents; and experience. Subsequently, a content analysis made it possible to identify common topics among them. [Results] The results showed that a teacher's self-efficacy was still in the process of development, far from what might be expected in teachers completing their initial training period. The need to increase the confidence of prospective teachers in their skills to translate knowledge of content into student learning, to implement different teaching strategies and, especially, to increase their confidence in their emotional skills is highlighted. [Conclusions] The results provide valuable information for teacher education programs by indicating the state of teacher self-efficacy at the end of the initial training period. In addition, a tool is provided to analyze the teaching self-efficacy of prospective Secondary Mathematics teachers. All this opens up future lines of research in various areas.